Pain relief and associated factors: a cross-sectional observational web-based study in a Quebec cohort of persons living with chronic pain - Zerriouh, Meriem; De Clifford-Faugère, Gwenaelle; Nguena Nguefack, Hermine Lore; Pagé, M. Gabrielle; Guénette, Line; Blais, Lucie; Lacasse, Anaïs (Frontiers in Pain Research, 2024)
Objectives: Randomized clinical trials are used to evaluate the efficacy of various pain treatments individually, while a limited number of observational studies have portrayed the overall relief experienced by persons living with chronic pain. This study aimed to describe pain relief in realworld clinical settings and to identify associated factors. Methods: This exploratory web-based cross-sectional study used data from 1,419 persons recruited in the community. Overall pain relief brought by treatments used by participants was assessed using a 0-100% scale (10-unit increments). Results: A total of 18.2% of participants reported minimal pain relief (0-20%), 60.0% moderate to substantial pain relief (30-60%), and 21.8% extensive pain relief (70-100%). Multivariable multinomial regression analysis revealed factors significantly associated with greater pain relief, including reporting a stressful event as circumstances surrounding the onset of pain, living with pain for ≥10 years, milder pain intensity, less catastrophic thinking, use of prescribed pain medications, use of nonpharmacological pain treatments, access to a trusted healthcare professional, higher general health scores, and polypharmacy. Factors associated with lower pain relief included surgery as circumstances surrounding pain onset, use of over-thecounter pain medications, and severe psychological distress. Discussion: In this community sample of persons living with chronic pain, 8 out of 10 persons reported experiencing at least moderate relief with their treatment. The analysis has enabled us to explore potential modifiable factors as opportunities for improving the well-being of persons living with chronic pain.